Training opportunities in grain post-harvest technology for developing countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Training opportunities in grain post-harvest technology for developing countries GASGA Joint Secretariat: GTZ, Post-Harvest Group, OE 4232, Postfach 5180, 65726 Eschborn, GERMANY